Robert L. Carlson, President of WFO shares his views on COP18 negotiations - CGIAR Research Program on Climate Change, Agriculture and Food Security (2012)
Robert L. Carlson, President of WFO (World Farmers Organisation) shares his views on COP18 negotiations Video by Meerim Shakirova